Liquid chemiluminescent DNA pull-down assay to measure nuclear receptor-DNA binding in solution. (October 2008) - Iwasaki, Toshiharu; Miyazaki, Wataru; Rokutanda, Nana; Koibuchi, Noriyuki
Electrophoretic mobility shift assays (EMSAs) are commonly used to investigate protein-DNA binding in vitro. However, EMSA can generate considerable amounts of undesirable waste, particularly when toxic compounds are examined. We therefore developed a novel in vitro protein-DNA binding assay called liquid chemiluminescent DNA pull-down assay, which is based on solution hybridization between digoxigenin-labeled DNA and glutathione S-transferase (GST)–fused DNA binding protein bound to glutathione-Sepharose beads.